Adherence to Treatment among Patients with Chronic Obstructive Pulmonary Disease in Erbil City - Dler Hamad Ismael; Sarhang Qadir Ibrahim; Chnar Salahaddin Qadir (Kufa Journal for Nursing Sciences)
Background : Chronic obstructive pulmonary disease is now widely recognized as a major global public health problem.